Decreased reelin expression in the left prefrontal cortex (BA9) in chronic schizophrenia patients - Habl, Gregor; Schmitt, Andrea; Zink, Mathias; Wilmsdorff, Martina Klara Pauline von; Jatzko, Alexander (Neuropsychobiology, 2012)
Background: Reelin is under epigenetic control and has been reported to be decreased in cortical regions in schizophrenia. Methods: To establish if expression of reelin is altered in specific cortical, hippocampal or thalamic regions of schizophrenia patients, we measured gene expression of reelin in a postmortem study of elderly patients with schizophrenia and non-affected controls in both hemispheres differentiating between gray and white matter. We compared cerebral postmortem samples (dorsolateral prefrontal cortex BA9 and BA46, superior temporal cortex BA22, entorhinal cortex BA28, sensoric cortex BA1-3, hippocampus, CA4, mediodorsal nucleus of the thalamus) from 12 schizophrenia patients with 13 normal subjects investigating gene expression of reelin in the gray and white matter of both hemispheres by in situ-hybridization. Results: The left prefrontal area (BA9) of schizophrenia patients revealed a decreased expression of reelin-mRNA of 29.1% in the white (p = 0.022) and 13.6% in the gray matter (p = 0.007) compared to the control group. None of the other regions examined showed any statistically significant differences. Conclusion: Since reelin is responsible for migration and synapse formation, the decreased gene expression of reelin in the left prefrontal area of schizophrenia patients points to neurodevelopmental deficits in neuronal migration and synaptic plasticity. However, our study group was small, and results should be verified using larger samples.
Gesehen am16.10.2018